Creación de un plan individual de autocuidados para la prevención del desgaste laboral en el personal técnico del centro de equidad y justicia Eloy Alfaro, durante el periodo de abril a julio del 2016. - Bedón Mafla, Sara Lucía (2017)
This degree work presents the systematization of the self-care individual plan creation for the decreasing of the compassion fatigue syndrome among the “Centro de Equidad y Justicia” professional staff, between April and June of 2016. The results of the intervention in the level of compassion fatigue are exposed, self-care activities role in dose results are shown, as well as the group process importance during the intervention and it achievements. The axis of the systematization is the concept and practice of self care. For the experience reconstruction there where used quantitative and qualitative tools. In one side, using the evaluation of the compassion fatigue syndrome with an accurate test (ProQOL). An estadistic description was made, between an initial evaluation and a final one. In the other side, a reconstruction trough registration files of each activity and participant observation was made, organized by information matrices; the qualitative information obtained was interpreted from a hermeneutical approach. These work concludes, from the quantitative results description as well as from the qualitative interpretation, that self-care promotion has an impact on the compassion fatigue levels and it works better when it is approached from a group perspective.